Feline plasma adrenocorticotropic hormone: validation of a chemiluminescent assay and concentrations in cats with hypercortisolism, primary hypoadrenocorticism and other diseases. Issue 2 (February 2021) - Tardo, Antonio M; Reusch, Claudia E; Galac, Sara; Fornetti, Sofia; Tirolo, Alessandro; Golinelli, Stefania; Shehdula, Dardan; Fracassi, Federico
Objectives: The aims of this study were to validate a commercially available chemiluminescent assay for measurement of feline plasma adrenocorticotropic hormone concentration (ACTH), to determine the normal reference interval (RI) of plasma ACTH in healthy cats, to assess plasma ACTH in cats with naturally occurring hypercortisolism (HC), primary hypoadrenocorticism (PH) and other diseases (OD), and to evaluate the effect of aprotinin on plasma ACTH degradation. Methods: Forty healthy cats, 10 with HC, 11 with PH and 30 with OD, were included. The chemiluminescent enzyme immunometric assay was evaluated by measurement of intra-assay precision, interassay precision and linearity. The RI for plasma ACTH in healthy cats was established using robust methods. Plasma ACTH of samples collected with and without aprotinin, stored at 4°C and assayed over a 6-day period, was measured. Results: The intra-assay coefficients of variance (CVs) ranged from 2.7% to 4.3% and interassay CVs from 3.3% to 10.7%. Dilution studies showed excellent accuracy (R 2 >0.99). The RI for plasma ACTH in healthy cats was 32–370 pg/ml. Plasma ACTH was not significantly different between healthy cats and the OD group. Cats with pituitary-dependent hypercortisolism (PDH) and PH had significantly higher plasma ACTH than the other groups. Plasma ACTH did not show significant differences when samples collected with and without aprotinin were compared. Conclusions and relevance: The Immulite chemiluminescent assay is a valid technique for measuring plasma ACTH in cats and the RI of plasma ACTH is quite wide. Owing to the low overlap between healthy or OD cats and cats with HC or PH, the measurement of plasma ACTH appears to be useful and should be included in the diagnostic work-up when HC or PH are suspected. Furthermore, the measurement of plasma ACTH may be an accurate test for differentiating PDH from adrenal-dependent hypercortisolism.